Potential of Cananga odorata and Citrus limon essential oils in modulating NOTCH1 signalling for non-melanoma skin cancer treatment - Muzamil, Muslihah; Azzam, Nur Ain; Mohd Radzuan, Hazulin; Wan Omar, Wan Fatein Nabeila (IIUM Journal of Orofacial and Health Sciences, 2025)
Natural products have drawn increasing attention as potential therapeutic agents, particularly for their anticancer properties. Essential oils (EOs) from Cananga odorata (CO) and Citrus limon (CL) are well-known for their antibacterial and antioxidant activities, yet their ability to suppress skin cancer cell growth remains uncertain. Whereas NOTCH1 signalling pathway plays an oncogenic role in cancer development due to uncontrolled cell proliferation. This study evaluates the antiproliferative effects of CO and CL EOs on skin cancer cells by examining their impact on NOTCH1 gene expression and protein secretion. Human foreskin fibroblast (HFF-1) and skin carcinoma (A431) cell lines were treated with DMSO-dissolved cisplatin and varying concentrations (125, 250, and 500 ?g/ml) of CO or CL EO for 24 hours. Cellular morphology was observed under 20–40x magnification, while qRT-PCR and western blot analyses were conducted to measure NOTCH1 gene expression and protein secretion. In A431 cells, CO EO at 125 ?g/ml significantly downregulated NOTCH1 gene expression compared to untreated cells, with levels lower than those induced by cisplatin. In contrast, CL EO at the same concentration upregulated NOTCH1 gene expression. At higher EO concentrations, both CO and CL EOs exhibited effects similar to cisplatin, with increased NOTCH1 protein secretion, likely resulting from apoptosis or necrosis-associated membrane leakage. These findings underscore the potential of natural products, particularly CO EO as an anticancer agent via modulation of NOTCH1 signalling. Further studies are essential to unravel the precise mechanisms by which these EOs affect A431 cells, advancing their potential use in skin cancer therapy.